2018
DOI: 10.1016/j.cmet.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Mitohormesis in Mice via Sustained Basal Activation of Mitochondrial and Antioxidant Signaling

Abstract: Transient mitochondrial stress can promote beneficial physiological responses and longevity, termed "mitohormesis." To interrogate mitohormetic pathways in mammals, we generated mice in which mitochondrial superoxide dismutase 2 (SOD2) can be knocked down in an inducible and reversible manner (iSOD2-KD mice). Depleting SOD2 only during embryonic development did not cause post-natal lethality, allowing us to probe adaptive responses to mitochondrial oxidant stress in adult mice. Liver from adapted mice had incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…These observations are in line with mitohormesis, a concept described in multiple organisms 18,57 whereby a moderate increase in ROS production, in the low micromolar range (Fig. 3f), promotes stress resistance and longevity 20,58 . This hypothesis is supported by recent literature pointing to the signaling role of ROS 16,17 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These observations are in line with mitohormesis, a concept described in multiple organisms 18,57 whereby a moderate increase in ROS production, in the low micromolar range (Fig. 3f), promotes stress resistance and longevity 20,58 . This hypothesis is supported by recent literature pointing to the signaling role of ROS 16,17 .…”
Section: Discussionsupporting
confidence: 85%
“…Growing evidence now indicates that ROS may also act as signaling molecules in physiological processes. Indeed, exposure for short time periods or low concentrations of ROS contributes to increased lifespan in multiple organisms [15][16][17] in a pro-survival mechanism called hormesis or mito-hormesis [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 and HO-1 expression is elevated in the heart, whereas the expression of UPR MT genes, Hsp60, ClpP, and Lonp1, is increased in skeletal muscle [67]. Cox et al revealed that the temporary depletion of SOD2 expression in embryogenesis potentiates Nrf2 signaling in later developmental stages [13]. The authors showed that inducible shRNA-mediated SOD2 knockdown during embryonic days 8.5-12.5 increased oxidative stress hallmarks and reduced aconitase activity without newborn lethality.…”
Section: Role Of Mtros and Nrf2 In Mitohormesismentioning
confidence: 99%
“…Bacterial infection stimulates macrophages to induce ROS production via NADPH oxidase, and mitochondria are used to eliminate • − ) produced in the mitochondrial matrix is readily reduced by SOD2 to hydrogen peroxide (H 2 O 2 ), which is then reduced by glutathione peroxidase (GPX) to water [12]. Short-term SOD2 depletion in mouse embryos increases mtROS; however, at the postnatal stage, it activates antioxidant defense by Nrf2 and remodels mitochondrial function in the liver [13]. In fibroblasts derived from Down syndrome patients, elevated mtROS production is counteracted by Nrf2, which is activated by PKCδ-mediated phosphorylation [14].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon indicated that conventional "toxic" drugs may have beneficial effects on cells. Evidence from both in vivo and in vitro studies has indicated that mild or sublethal mitochondrial stress from chemicals, especially some mitochondria-targeted drugs, showed beneficial effects on cells and organisms against larger subsequent stresses-induced damages or death (Cox et al 2018;Obata et al 2018;Yuyun et al 2012;De Haes et al 2014). This response activated by a moderate mitochondrial stress has been named mitohormesis, and it can maintain cellular homeostasis and extend lifespan (Tapia 2006;Yun and Finkel 2014).…”
Section: Introductionmentioning
confidence: 99%